Subjective evaluation of monopolar radiofrequency treatment by patients in aesthetic rejuvenation - Hwang, Yousun; Arayaskul, Smith; Vachiramon, Vasanop; Yi, Kyu‐Ho (Skin research and technology, 2024)
Objective To assess the subjective experiences of patients following monopolar radiofrequency (RF) treatment for facial rejuvenation and anti‐aging purposes. Methods A study involving 50 female patients (aged 30–70 years, Fitzpatrick skin type III and IV) who received a single session of RF treatment. Exclusion criteria comprised active infections, skin diseases, pregnancy, or history of recent anti‐aging treatments. Thirty‐four patients completed a 10‐question questionnaire after 3 months of treatment. Results Among the respondents, 82% expressed satisfaction with the RF treatment, reporting significant improvements primarily in the mid and lower face, and eyelids. Mainly, patients noted improvements in skin laxity (52.9%), skin texture (17.6%), and skin tone (11.7%). Notably, 73.5% noticed changes within 1–2 months post‐treatment, with the peak effect observed at 1–2 months. Mild complications (swelling and erythema) were reported, usually resolving within a week. The mean pain score was 1.94 (±0.66), indicating mild to moderate discomfort. Discussion Monopolar RF devices, apply high‐frequency electric currents generating heat, stimulating collagen production for skin tightening. This study's unique focus on detailed subjective patient experiences provides insights valuable in clinical settings, aiding clinicians in managing patient expectations and achieving optimal results. The satisfaction rates align with previous findings, emphasizing RF treatment's efficacy in addressing facial laxity, especially in the mid and lower face. Positive feedback extended beyond skin tightening, encompassing skin texture and tone improvements. While the study's observation period was 3 months post‐treatment, longer‐term studies are warranted for comprehensive assessments. Conclusion The study underscores the efficacy of monopolar RF device, as a non‐invasive and effective anti‐aging treatment. The findings contribute to diversifying the RF market, potentially aiding clinicians in optimizing patient care. Considering the growing complexity of patient demands and treatment responses, this study serves as a valuable reference for clinicians engaging in RF treatments.